Application of fluorinated COF magnetic composite material in mycotoxin adsorption
By using the fluorinated COF magnetic composite material Fe3O4@TAPT-COF-4F that is closely attached to nano Fe3O4 particles as an adsorption material, the problem of easy blockage of solid phase extraction column is solved, and efficient and economical fungal toxin enrichment purification and detection is achieved. .
Patent Information
- Application Number
- CN202411438742.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing mycotoxin detection methods, the solid-phase extraction column is prone to blockage, resulting in the sample quality not reaching the detection limit, and the detection efficiency is low and the cost is high, so complex samples cannot be effectively processed.
Using nano Fe3O4 particles as the core and closely adhered to 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 2,3,5,6-tetrafluoroterephthaldehyde The fluorinated COF magnetic composite material Fe3O4@TAPT-COF-4F of the covalent organic frame material layer formed by polycondensation is enriched and purified by the adsorption material by magnetic solid phase extraction.
This material has high adsorption capacity, good hydrophilicity, short adsorption equilibrium time and strong anti-matrix interference ability, which significantly improves the adsorption and extraction efficiency of mycotoxins, reduces detection costs, and can be reused multiple times.
Smart Images

Figure BDA0005085795700000081 
Figure BDA0005085795700000101 
Figure BDA0005085795700000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material application, and in particular to the application of a fluorinated COF magnetic composite material in the adsorption of fungal toxins. Background Art
[0002] Mycotoxins are metabolites produced by fungi growing in food or feed, which are extremely harmful to humans and animals. Among them, aflatoxins (such as AFB1, AFB2, AFM1, AFG1, AFG2) are the most common. Existing mycotoxin detection mainly adopts liquid chromatography (HPLC) fluorescence detection method, liquid chromatography-mass spectrometry (HPLC-MS / LC-MS) detection method, enzyme-linked immunosorbent assay (ELISA), etc. According to different samples and detection targets, appropriate sample treatment methods are generally used in advance before instrumental analysis. The common sample treatment method is mainly solid phase extraction, which uses solid phase extraction agents to enrich and purify the detection target from the sample to reduce the interference of other substances in the sample on the detection results of the detection target. Currently, the commonly used solid phase extraction agents are mostly commercially available solid phase extraction columns filled with adsorbent materials. When faced with samples with complex ingredients such as food or feed, the solid phase extraction columns are severely clogged during the purification process, reducing the sample quality and failing to meet the detection limit standard. In addition, the solid phase extraction columns have technical problems such as serious compound loss, poor repeatability of test results, time-consuming and labor-intensive, high cost, inability to test large quantities of samples, and low efficiency.
[0003] Covalent organic framework materials (COFs, abbreviated as COF) are organic porous materials with an ordered crystalline structure and uniform pore size, so they are also called "organic zeolites". Compared with inorganic porous materials, COF also has the common advantages of other porous organic framework (POFs) materials: (1) The building blocks are small organic molecules with a wide range of sources and types, which makes the building blocks diverse and facilitates the regulation of the structure and function of the target material through the building blocks; (2) The spatial network structure is formed by covalent bonds and has good thermal and chemical stability; (3) It is composed of light elements (C, H, O, N and B, etc.) and has a low density. At present, magnetic covalent organic framework materials are increasingly used in enrichment and purification pretreatment. For example, Chinese patent ZL2022112583299 discloses a magnetic dispersed solid phase extractant for simultaneous enrichment and purification of nine fungal toxins. The solid phase extractant is a spherical magnetic triazine-based covalent organic framework material Fe3O4@COF(TAPT-DHTA) composed of nano-Fe3O4 particles and a covalent organic framework material formed by 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 2,5-dihydroxyterephthalic acid. Fe3O4@COF(TAPT-DHTA) nanomaterial is used as a magnetic adsorbent to perform magnetic solid phase extraction of nine common fungal toxins in fruit products in a sample solution at pH = 3.0-6.0 (preferably pH = 4.0). An efficient, high recovery and low-cost nano pretreatment method is established to overcome the problems of high matrix effect, time-consuming pretreatment and poor purification effect in traditional methods. If the types of adsorbents suitable for mycotoxins can be expanded, it will be beneficial to the detection of mycotoxins in complex samples. Summary of the invention
[0004] The present invention provides an application of a fluorinated COF magnetic composite material in adsorbing fungal toxins. The fluorinated COF magnetic composite material can specifically bind to fungal toxins.
[0005] A fluorinated COF magnetic composite material is used in the adsorption of fungal toxins. The structural formula of the fluorinated COF magnetic composite material is Fe3O4@TAPT-COF-4F (i.e., 4F-COF@Fe3O4), which is based on nano-Fe3O4 particles as the core and tightly attached to the nano-Fe3O4 particles are covalent organic framework material layers formed by condensation polymerization of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT) monomers and 2,3,5,6-tetrafluoroterephthalaldehyde (4F-PDA) monomers connected by imine bonds.
[0006] The fluorinated COF magnetic composite material can be directly used as an adsorbent material for adsorbing mycotoxins, or can be used to prepare an adsorbent material for adsorbing mycotoxins. For example, the mycotoxins in the enriched and purified samples can be used in the sample pretreatment during mycotoxin detection to reduce the interference of other substances and ensure that the detection data is accurate and reliable.
[0007] The mycotoxins include aflatoxins (AFs), etc. The aflatoxins include one or more of aflatoxin M1 (AFM1), aflatoxin B1 (AFB1), aflatoxin B2 (AFB2), aflatoxin G1 (AFG1), aflatoxin G2 (AFG2), etc.
[0008] Preferably, the molar ratio of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomer to the 2,3,5,6-tetrafluoroterephthalaldehyde monomer is 1:1-1.5.
[0009] Preferably, the method for preparing the fluorinated COF magnetic composite material comprises:
[0010] Mix 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 2,3,5,6-tetrafluoroterephthalaldehyde, o-dichlorobenzene and n-butanol, add aniline while mixing, mix well; then add nano Fe3O4, mix well while adding; then take a mixed solution of Fe(NO3)3 and n-butanol, add in small amounts multiple times, mix well before and after each addition, ultrasonicate for 1h-1.5h after all are added, then stand at 60℃-80℃ (most preferably 70℃) for at least 24h (most preferably 24h), wash and dry the product to obtain Fe3O4@TAPT-COF-4F material. The preparation method can prepare Fe3O4@TAPT-COF-4F material with nano Fe3O4 particles as the core and a covalent organic framework material layer formed by condensation of TAPT monomer and 4F-PDA monomer connected by imine bonds tightly attached to the nano Fe3O4 particles.
[0011] Preferably, the molar ratio of the nano-Fe3O4 to the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomer is 2.5-5:1, and more preferably 3:1.
[0012] The o-dichlorobenzene and n-butanol are used as reaction solvents, and their usage amounts are not particularly limited. The usage amounts are preferably such that the monomers can be placed in the reaction solvent.
[0013] The aniline acts as a cut-off agent.
[0014] The Fe(NO3)3 is a reaction catalyst.
[0015] Preferably, the step of adding the mixture of Fe(NO3)3 and n-butanol in small amounts multiple times may include: adding in three times, shaking before and after each addition, the first addition amount accounting for one-fifth to one-quarter of the total volume of the mixture of Fe(NO3)3 and n-butanol, and mixing; the second addition amount accounting for one-fifth to one-quarter of the total volume of the mixture of Fe(NO3)3 and n-butanol, and mixing; the third addition amount accounting for the remainder and mixing.
[0016] The washing comprises washing with ethanol, pure water, ethanol, tetrahydrofuran, and n-hexane in sequence, and then soaking with n-hexane.
[0017] The drying is carried out by drying, vacuum drying, etc., and the drying temperature is preferably 50° C.-65° C. For example, the drying may be carried out for 30 minutes, and then vacuum drying may be carried out for at least 3 hours.
[0018] The application method includes a sample pre-treatment method, for example: a sample treatment method for mycotoxin detection, comprising the steps of:
[0019] The sample is extracted with an acetonitrile aqueous solution to obtain a sample extract, which is then blown dry and redissolved with water to obtain a sample solution, the pH of which is adjusted to 5-8, the fluorinated COF magnetic composite material is added and mixed evenly for adsorption, and then the fluorinated COF magnetic composite material is separated using an external magnetic field; the fluorinated COF magnetic composite material separated using the external magnetic field is taken out after being eluted and desorbed by an eluent, and the eluent after desorption is used as a treated sample.
[0020] The sample includes one or more of food samples, feed samples, etc. For example, samples of corn, rice, oats, soybeans, wheat, bananas, milk, edible oil, etc., including but not limited to one or more of wheat (such as wheat flour), corn (such as corn flour), corn silage, oats (such as oat flour), rice (such as rice flour), soybeans (such as soybean flour), bananas, milk, edible oil (such as rapeseed oil), etc.
[0021] The acetonitrile aqueous solution is used as an extracting solution, and the amount used is preferably such that the sample can be placed in the extracting solution, preferably at least 2 mL is used per milligram of sample, and increasing the amount of the extracting solution has no adverse effect on the extraction. From the perspective of cost saving, it is further preferred to use 2 mL-3 mL per milligram of sample. The volume percentage concentration of acetonitrile in the acetonitrile aqueous solution is preferably 80%. The extraction time is preferably ultrasonic extraction for 30 min-35 min. The ratio of the volume of water added during the water reconstitution to the volume of the sample extract after drying is preferably 1-2:1.
[0022] Preferably, the amount of the fluorinated COF magnetic composite material used in each milliliter of sample solution is 1 mg or more, more preferably 2 mg or more, and most preferably 3 mg while taking into account both the adsorption effect and the saving of raw materials.
[0023] Preferably, the pH value of the sample solution is adjusted to 6-8, most preferably 7, and the fluorinated COF magnetic composite material has a better adsorption effect on fungal toxins. The pH regulator used to adjust the pH is selected from one or more of ammonia solution, acetic acid solution, etc.
[0024] Preferably, the adsorption time is 5 seconds or longer, more preferably 15 seconds or longer, and most preferably 15 seconds.
[0025] Preferably, the eluent is selected from one of acetonitrile, acetonitrile aqueous solution, and acetonitrile acetic acid aqueous solution. Further preferably, the volume ratio of acetonitrile to water in the acetonitrile aqueous solution is 80-90:10-20. Further preferably, the volume ratio of acetonitrile (ACN), water and acetic acid (HAc) in the acetonitrile acetic acid aqueous solution is 80-90:8-18:1-2.
[0026] Preferably, the desorption time is more than 1 min, more preferably more than 2 min, and most preferably 2 min-3 min.
[0027] The fluorinated COF magnetic composite material can be reused. The desorbed fluorinated COF magnetic composite material can be reused after washing, and can be reused at least 10 times.
[0028] A method for detecting mycotoxins, using a treated sample obtained by the sample processing method for detecting mycotoxins as a test sample, and using the method for detecting mycotoxins to detect the mycotoxins in the test sample.
[0029] The mycotoxin detection method may be an existing mycotoxin detection method, or a detection method that is simply optimized on the existing mycotoxin detection method, for example: one or more of liquid chromatography (HPLC) fluorescence detection method, liquid chromatography-mass spectrometry (HPLC-MS / LC-MS) detection method, enzyme-linked immunosorbent assay (ELISA), etc.
[0030] The raw materials, reagents, instruments, etc. used in the present invention can all be commercially available products.
[0031] The present invention has the following beneficial effects:
[0032] The present invention is the first to discover that the fluorinated COF magnetic composite material Fe3O4@TAPT-COF-4F, which has nano-Fe3O4 particles as the core and a covalent organic framework material layer formed by the condensation of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomers and 2,3,5,6-tetrafluoroterephthalaldehyde monomers connected by imine bonds, is tightly attached to the nano-Fe3O4 particles and has good adsorption performance for fungal toxins such as aflatoxin, and can be used for the enrichment and purification of fungal toxins such as aflatoxin.
[0033] The 4F-COF-TAPT@Fe3O4 of the present invention has high adsorption capacity, good hydrophilicity, short adsorption equilibrium time, strong anti-matrix interference ability, good stability in the adsorption and extraction process, and has the advantages of fast separation speed, high adsorption and extraction efficiency, and many recycling times. The adsorption capacity, adsorption efficiency, desorption efficiency, etc. of the existing Fe3O4@COF (TAPT-DHTA) material are significantly improved.
[0034] The present invention successfully prepares a fluorinated COF magnetic material with high specific surface area, uniform pore size, stability and functionalization through a one-pot method, which has the advantages of simple synthesis, short reaction time, mild reaction conditions, short preparation time, no need for multiple reactions, and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a Fourier transform infrared spectrum (FT-IR) diagram of 4F-COF@Fe3O4, raw material 4F-PDA and raw material TAPT of the present invention;
[0036] Figure 2 This is the N2 isothermal adsorption-desorption curve of 4F-COF@Fe3O4 of the present invention;
[0037] Figure 3 This is the X-ray diffraction (XRD) characteristic diagram of 4F-COF@Fe3O4 of the present invention;
[0038] Figure 4 This is the hysteresis curve of 4F-COF@Fe3O4 of the present invention;
[0039] Figure 5 This is a scanning electron microscope (SEM) image of 4F-COF@Fe3O4 of the present invention;
[0040] Figure 6 This is a transmission electron microscope (TEM) image of 4F-COF@Fe3O4 of the present invention;
[0041] Figure 7 This is the effect of different adsorption material dosage on recovery rate;
[0042] Figure 8 This is the effect of different eluents on the recovery rate;
[0043] Fig. 9 This is the effect of different adsorption time on the extraction rate;
[0044] Fig.10 This is the effect of different desorption time on recovery rate;
[0045] Fig.11 This is the effect of different pH on recovery rate;
[0046] Fig.12 This is a graph showing the effect of repeated use of 4F-COF@Fe3O4 on the recovery rate of the present invention;
[0047] Fig.13 This is a schematic diagram of the synthesis route of 4F-COF@Fe3O4 of the present invention.
[0048] Transmittance is transmittance, Wavenumbers is wave number, Quantity Adsorbed (cm 3 / g STP) is the adsorption amount, Relative Pressure is the relative pressure, dV / dD Pore Volume is the pore volume under unit pore diameter, Pore Diameter is the pore diameter, Adsorption is adsorption, Desorption is desorption, Intensity is intensity, 2-Theta (degree) is 2-θ (degree), Magnetization is magnetization, Magnetic Field is magnetic field, Recovery is recovery rate, Adsorbent dosage (mg) is adsorbent dosage (milligrams), Eluent is eluent, Extraction ratio (%) is extraction rate, Adsorption time (second) is adsorption time (seconds), Desorption time (min) is desorption time (minutes), Reusable times is the number of reusable times. DETAILED DESCRIPTION
[0049] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand the technical solutions of the present invention.
[0050] Experimental Materials:
[0051] Ethanol, pure water, tetrahydrofuran, n-hexane, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 2,3,5,6-tetrafluoroterephthalaldehyde, o-dichlorobenzene, n-butanol, benzaldehyde, aniline, ferrous oxide (Fe3O4), ferric nitrate (Fe(NO3)3), and ammonium acetate; all are commercially available products.
[0052] Example 1 Preparation of Materials
[0053] Weigh 75 mg ± 3 mg (0.21 mmol ± 0.01 mmol) of TAPT, 58 mg (0.28 mmol) of 2,3,5,6-tetrafluoroterephthalaldehyde, 20 mL of o-dichlorobenzene and 15 mL of n-butanol into a round-bottom flask, shake well, and add aniline (36 mL) while ultrasonically mixing; then add nano-Fe3O4 (150 mg, 0.65 mol, particle size of 30 nm-40 nm), and shake well while ultrasonically adding to prevent Fe3O4 from sticking to the bottom of the flask.
[0054] Take 30 mg of Fe(NO3)3 and 5 mL of n-butanol, mix them by ultrasonication and add them to the flask three times. Shake well before and after adding each reagent. Add 1 mL for the first time and ultrasonicate for 5 minutes. Add 1 mL for the second time and ultrasonicate for 5 minutes. Add 3 mL for the third time. After the above operation is completed, ultrasonicate for 1 hour and then stand in an oil bath at 70°C for 24 hours. The product is washed and dried to obtain Fe3O4@TAPT-COF-4F (i.e.: 4F-COF@Fe3O4) material.
[0055] Washing: Each washing should be ultrasonic and hand-shaked for 30 seconds. The order of washing solutions: ethanol wash twice → pure water wash twice → ethanol wash once → tetrahydrofuran wash twice → n-hexane wash once → n-hexane soak for 20 minutes.
[0056] Drying: First dry in a drying oven at 60°C for 30 min, then vacuum dry at 60°C for 3 h.
[0057] Figure 1 The FT-IR spectrum shows that: the NH stretching vibration peak is observed in the raw material TAPT; the C=O stretching vibration peak is observed in the raw material 2,3,5,6-tetrafluoroterephthalaldehyde; however, in the product 4F-COF@Fe3O4, the NH stretching vibration peak and the C=O stretching vibration peak are not observed. Instead, the -C=N- peak is observed, indicating that the covalent organic framework material 4F-COF@Fe3O4 formed by the condensation of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomer and 2,3,5,6-tetrafluoroterephthalaldehyde monomer connected by imine bonds is successfully synthesized. The structural unit of 4F-COF@Fe3O4 is shown in FIG. Fig.13 .
[0058] The material was degassed at 395K for 5 h, and then the N2 isothermal adsorption-desorption curve of the material was measured using a fully automatic specific surface area and micropore physical adsorption and chemical adsorption analyzer (Micromeritics ASAP 2460). The N2 isothermal adsorption-desorption curve of 4F-COF@Fe3O4 is shown in Figure 2 The pore sizes are mostly distributed in a few nanometers. The specific surface area of 4F-COF@Fe3O4 calculated by BET method is 940m 2 / g. In addition, the N2 isotherm adsorption-desorption curve of 4F-COF@Fe3O4 belongs to the IV type curve, indicating that the COF has a mesoporous structure (pore size is 2nm-52nm). And the average pore size of 4F-COF@Fe3O4 calculated by the BJH method is 2.5nm.
[0059] The XRD pattern of 4F-COF@Fe3O4 is shown in Figure 3 The crystal structure of 4F-COF@Fe3O4 was determined by XRD diffraction. The characteristic diffraction peaks at 2θ of 2.8°, 30.1°, 35.5°, 43.1°, 53.5°, 57° and 62.1° correspond to the crystallization of Fe3O4, which proves the magnetization and crystallization of 4F-COF@Fe3O4.
[0060] The magnetization intensity of 4F-COF@Fe3O4 was tested by vibrating sample magnetometer (VSM). The test results are shown in Figure 4 The hysteresis curve showed that the saturation magnetization intensity of 4F-COF@Fe3O4 was 60emu / g, showing strong magnetism and superparamagnetism. The results proved that 4F-COF@Fe3O4 can react with external magnetic fields.
[0061] The SEM image of 4F-COF@Fe3O4 is shown in Figure 5 The SEM image shows the morphology of 4F-COF@Fe3O4. The surface is rough and spherical, the particle size is 50nm-60nm, and there is a certain agglomeration phenomenon, but it has little effect on the adsorption effect.
[0062] TEM image of 4F-COF@Fe3O4 is shown in Figure 6 The TEM image shows that a close structure is formed between Fe3O4 and COF in 4F-COF@Fe3O4, that is, the nano-Fe3O4 particles are the core and a covalent organic framework material (COF) layer formed by the condensation of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomer and 2,3,5,6-tetrafluoroterephthalaldehyde monomer connected by imine bonds is tightly attached to the nano-Fe3O4 particles.
[0063] Example 2
[0064] Sample preparation:
[0065] Take 5 mg of sample (including blank sample, spiked sample and actual sample to be tested), add 15 mL of acetonitrile aqueous solution (acetonitrile to water ratio: 80 / 20, v / v), vortex for 5 min and then ultrasonically extract for 30 min to obtain the sample extract, then blow it nearly dry with nitrogen, and store it in a -20°C refrigerator. When using, place it at room temperature, and then dissolve it with water with a volume twice the volume of the sample extract after drying to obtain the sample solution.
[0066] Adsorption: The sample solution was placed in an ep tube to adjust the pH, and the fluorinated COF magnetic composite material 4F-COF@Fe3O4 in Example 1 was added to the ep tube, mixed evenly, and vortexed for adsorption, and 4F-COF@Fe3O4 was separated by an external magnet.
[0067] Desorption: The 4F-COF@Fe3O4 separated by the external magnet is taken out after desorption by the eluent, and the eluent after desorption is used as the treated sample. The treated sample is used as the test sample, and the mycotoxin in the test sample is detected by the mycotoxin detection method. The treated sample is treated by a membrane (glass fiber membrane) and then analyzed by the instrument.
[0068] HPLC instrument analysis conditions:
[0069] Mobile phase: 5mM (mmol / L) ammonium acetate aqueous solution in phase A, acetonitrile in phase B, gradient elution, gradient elution program: initial (0 minutes) 80% A and 20% B, 5 minutes 5% A and 95% B, 6 minutes 80% A and 20% B, all volume percentages. Flow rate set to 0.4mL / min. Injection volume 1μL, single sample detection time 10 minutes. Flow rate 0.4mL / min. Chromatographic column: Titank C183u 150*3mm. Column temperature: 40℃. Target detection conditions are shown in Table 1:
[0070] Table 1
[0071]
[0072] Example 3
[0073] AFM1, AFB1, AFB2, AFG1, and AFG2 were used to prepare aqueous solutions of mycotoxin standards, each with a concentration of 5 ppb, as sample solutions. The adsorption, desorption, and instrumental analysis in Example 2 were used for the experiment.
[0074] 1. Optimization of M-SPE conditions
[0075] 1.1. Amount of adsorption material
[0076] The amount of adsorbent material has a significant effect on the efficiency of M-SPE. In order to ensure that AFs has sufficient M-SPE material, the sample solution has a natural pH, and 1 mg-5 mg 4F-COF@Fe3O4 is added to each milliliter of sample solution. The effect of the amount of the adsorbent material 4F-COF@Fe3O4 of the present invention in the range of 1 mg-5 mg on the efficiency of M-SPE is investigated. The adsorption time is 15 seconds, and the eluent is an acetonitrile acetic acid aqueous solution, in which the volume ratio of ACN / H2O / HAc is 90 / 9 / 1, and the desorption time is 3 minutes.
[0077] like Figure 7 As shown, when the amount of adsorbent material is 1mg-5mg, the recovery rates of AFB1, AFB2, AFG1, AFG2, and AFM1 are 85.16%-123.45%; when the amount of adsorbent material is 3mg, the recovery rates of AFM1 and AFG1 are 104.66% and 101.73%, respectively, and the recovery rates of AFB1, AFB2, and AFG2 are 112.58%, 107.59%, and 113.33%, respectively, which are closest to 100%, indicating the best adsorption effect. Further increasing the amount of adsorbent material does not significantly improve the adsorption effect. Considering comprehensively, it is preferred that the amount of adsorbent material per milliliter of sample solution is more than 1mg, and more preferably more than 2mg. Under the premise of taking into account the adsorption effect and saving raw materials, 3mg is most preferred.
[0078] 1.2. Elution buffer
[0079] Selecting a suitable elution solvent to transfer the adsorbed target from the adsorbent material to the elution solvent is a key step in M-SPE. The sample solution has a natural pH, 3 mg 4F-COF@Fe3O4 is added to each milliliter of the sample solution, the adsorption time is 15 seconds, the desorption time is 3 minutes, and the eluent is acetonitrile, acetonitrile aqueous solution (ACN / H2O volume ratio is 90 / 10), and acetonitrile acetic acid aqueous solution (ACN / H2O / HAc volume ratio is 90:9:1 or 90:8:2).
[0080] like Figure 8 As shown, when acetonitrile, acetonitrile aqueous solution (ACN / H2O volume ratio of 90 / 10), and acetonitrile acetic acid aqueous solution (ACN / H2O / HAc volume ratio of 90:9:1 or 90:8:2) are used as eluents, the recovery rates of the five fungal toxins are between 96.3% and 120.4%, which have good desorption capacity and can be used as eluents of the present invention.
[0081] This may be due to the polarity of ACN compared with the eluents methanol, ethanol, ethyl acetate, and dichloromethane, and the hydrogen bond interaction between the adsorbate (AFs as hydrogen bond donors) and the adsorbent material (4F-COF@Fe3O4 as hydrogen bond acceptors), so it can effectively desorb AFs from the adsorbent material based on the "like dissolves like" principle and hydrogen bond effect. Therefore, the present invention selects one of acetonitrile, acetonitrile aqueous solution, and acidic ACN (e.g., acetonitrile acetic acid aqueous solution) as the eluent. Further preferably, the volume ratio of ACN to water in the acetonitrile aqueous solution is 80-90:10-20. Further preferably, the volume ratio of ACN, water, and HAc in the acetonitrile acetic acid aqueous solution is 80-90:8-18:1-2.
[0082] 1.3. Adsorption time and elution time
[0083] The adsorption time was explored in the range of 5s-120s. The sample solution had a natural pH, 3mg 4F-COF@Fe3O4 was added to each milliliter of the sample solution, and the eluent was acetonitrile acetic acid aqueous solution (ACN / H2O / HAc volume ratio was 90:9:1), and the desorption time was 3min.
[0084] like Fig. 9 As shown, the adsorption efficiency (i.e., extraction rate) of 4F-COF@Fe3O4 for AFs can reach 63.38%-80.50% when the adsorption time is 5s, and it increases rapidly to nearly 100% when the adsorption time is 15s. When the adsorption time is extended from 15s to 120s, the adsorption efficiency shows a stable platform with little change. Therefore, the adsorption time is preferably more than 5 seconds, more preferably more than 15 seconds, and most preferably 15 seconds. The adsorption efficiency, i.e., the extraction rate, is calculated according to the following formula (I):
[0085]
[0086] In formula (I), m is the mass of the adsorbent material (mg), C0 is the initial concentration of each AFs in the sample solution (mg / L), Ce is the final concentration of each AFs in the sample solution after adsorption by the adsorbent material (mg / L), and V is the volume of the sample solution (L).
[0087] In addition, the sample solution was at natural pH, 3 mg 4F-COF@Fe3O4 was added to each ml of sample solution, acetonitrile and acetic acid aqueous solution (ACN / H2O / HAc volume ratio of 90:9:1) was used as eluent, the adsorption time was 15 s, and the desorption time was studied in the range of 1 min-5 min.
[0088] like Fig.10 As shown in the figure, as the desorption time increases from 1 min to 3 min, the M-SPE recovery rate of 4F-COF@Fe3O4 for AFs gradually increases, and the recovery rate is stable when the desorption time is more than 3 min. Therefore, the desorption time is preferably more than 1 min, more preferably more than 2 min, and most preferably 2 min-3 min.
[0089] 1.4.pH
[0090] The present invention finds that pH value affects the existence state of AFs and the surface properties of 4F-COF@Fe3O4, thereby affecting the adsorption performance of 4F-COF@Fe3O4 on AFs. The pH value of the sample solution is adjusted to 5-8 using an aqueous ammonia solution and / or an aqueous HAc solution, and then 3 mg of 4F-COF@Fe3O4 is added per milliliter to the sample solution with the adjusted pH value, and an acetonitrile acetic acid aqueous solution (ACN / H2O / HAc volume ratio of 90:9:1) is used as the eluent, and the adsorption time is 15 seconds and the desorption time is 3 minutes for the study.
[0091] like Fig.11 As shown in the figure, when the pH is 6-8, the recovery rate of 4F-COF@Fe3O4 for AFs is close to 100%, and the effect is good; when the pH is 7, the recovery rate of 4F-COF@Fe3O4 for AFs is closest to 100%, and the effect is best. Therefore, it is preferred to adjust the pH value of the sample solution to 5-8, more preferably 6-8, and most preferably 7, so that the fluorinated COF magnetic composite material has a better adsorption effect on fungal toxins in the sample solution.
[0092] 1.5 Number of times of repeated use
[0093] The reusability of 4F-COF@Fe3O4 is an important indicator of cost saving. Through multiple M-SPE experiments under the same conditions: 3 mg of 4F-COF@Fe3O4 was added to each milliliter of sample solution, acetonitrile and acetic acid aqueous solution (ACN / H2O / HAc volume ratio is 90:9:1) was used as eluent, the adsorption time was 15 seconds, and the desorption time was 3 minutes; the reusability of 4F-COF@Fe3O4 was investigated from the perspective of extraction recovery rate. Fig.12 As shown, even after 10 consecutive uses, the recovery rate of 4F-COF@Fe3O4 can still reach more than 68%, indicating its good reusability.
[0094] 2. Method Validation
[0095] The sample pretreatment and detection were carried out according to Example 2, wherein: the pH of the sample solution was adjusted to 7, 3 mg of adsorbent material was added per ml of sample solution, the adsorption time was 15 seconds, the eluent was acetonitrile acetic acid aqueous solution, wherein the volume ratio of ACN, water and HAc was 90:9:1, and the desorption time was 3 min. 2), limits of detection (LODs, i.e., LOD), limits of quantification (LOQs, i.e., LOQ), and repeatability. LODs and LOQs were calculated at signal-to-noise ratios (S / N) of 3 and 10, respectively. In order to eliminate matrix effects (MEs), seven different concentration levels (0.01 μg / kg-50 μg / kg) were introduced into soybean, corn, rice, oat, sweet potato, banana, milk, and rapeseed oil samples that did not contain AFs to establish matrix-matched calibration curves. As shown in Table 2, soybean, sweet potato, oat, banana, corn, and whole-fat liquid milk samples had good linear relationships in the range of 0.01 μg / kg-50 μg / kg, and rice and rapeseed oil samples had good linear relationships in the range of 0.025 μg / kg-50 μg / kg; R 2 The detection limits of soybeans are 0.002μg / kg-0.029μg / kg, bananas are 0.003μg / kg-0.026μg / kg, sweet potatoes are 0.001μg / kg-0.019μg / kg, oats are 0.001μg / kg-0.027μg / kg, whole milk are 0.001μg / kg-0.024μg / kg, corn are 0.001μg / kg-0.022μg / kg, rice are 0.006μg / kg-0.017μg / kg, and rapeseed oil are 0.006μg / kg-0.017μg / kg. The LOQs of soybeans and bananas were 0.010μg / kg-0.100μg / kg, those of whole milk were 0.010μg / kg-0.080μg / kg, those of sweet potatoes and corn were 0.010μg / kg-0.075μg / kg, those of rapeseed oil were 0.025μg / kg-0.10μg / kg, those of rice were 0.025μg / kg-0.060μg / kg, and those of oats were 0.010μg / kg-0.10μg / kg. The spiked samples (AFs standard was added to soybean, corn, rice, oat, sweet potato, banana, milk and rapeseed oil samples without AFs) of 5μg / kg, 10μg / kg and 30μg / kg were analyzed 3 times on the same day and for more than 3 consecutive days, and the intra-day and inter-day relative standard deviation (RSD) values and average recovery rates were obtained. The intra-day RSD was less than 9.4%; the inter-day RSD of corn was less than 4.92%. The results showed that the method established by the present invention has good accuracy and precision and can be used for the detection of AFs in food samples.
[0096] Table 2 Linear range, linear equation, LODs, LOQs, matrix effects, precision and recovery (n = 3)
[0097]
[0098]
[0099] 3. Actual sample testing
[0100] The applicability of the method was evaluated by analyzing AFs in several field samples of cereals (corn, rice, soybean, sweet potato, oat), fruits (banana), edible oil (rapeseed oil) and milk (whole milk). Sample pretreatment and detection were performed according to Example 2, wherein: the pH of the sample solution was adjusted to 7, 3 mg of 4F-COF@Fe3O4 in Example 1 was added per ml of sample solution, the adsorption time was 15 seconds, and the eluent was acetonitrile acetic acid aqueous solution, wherein the volume ratio of ACN, water and HAc was 90:9:1, and the desorption time was 3 minutes. 0.9 μg / kg of AFB1 was detected in the corn sample (which did not exceed the residue limit of 2 μg / kg in corn stipulated by China and the European Union), and no residues of AFs were identified in other samples.
[0101] Comparative Example 1
[0102] Fe3O4@COF (TAPT-DHTA) containing a COF layer composed of TAPT monomer and 2,5-dihydroxyterephthalic acid (DHTA) monomer was prepared using Example 1 of Chinese patent application CN2022112583299.
[0103] By using the method in Example 1 of Chinese patent application CN2022112583299, the DHTA monomer is replaced with 2,3-dihydroxyterephthalaldehyde to obtain Fe3O4@TAPT-COF-OH containing a COF layer composed of TAPT monomer and 2,3-dihydroxyterephthalaldehyde monomer.
[0104] By using the method in Example 1 of Chinese patent application CN2022112583299, the DHTA monomer is replaced with 2,5-divinylterephthalaldehyde to obtain Fe3O4@TAPT-COF-C2H4 containing a COF layer composed of TAPT monomer and 2,5-divinylterephthalaldehyde monomer.
[0105] By using the method in Example 1 of Chinese patent application CN2022112583299, the DHTA monomer is replaced with 2,5-dimethoxyterephthalaldehyde to obtain Fe3O4@TAPT-COF-MeO containing a COF layer composed of TAPT monomer and 2,5-dimethoxyterephthalaldehyde monomer.
[0106] The average recovery rates of magnetic solid phase extraction (M-SPE) with different adsorbents were compared. M-SPE extraction conditions: AFM1, AFB1, AFB2, AFG1, and AFG2 standards were added to corn flour without AFs to concentrations of 10 ppb, 10 ppb, 10 ppb, 10 ppb, and 10 ppb, respectively. Sample pretreatment and detection were performed according to Example 2, wherein: the pH of the sample solution was adjusted to 7, 3 mg of adsorbent material was added per milliliter of sample solution, the adsorption time was 15 seconds, and the eluent was acetonitrile acetic acid aqueous solution, wherein the volume ratio of ACN, water, and HAc was 90:9:1, and the desorption time was 3 min. The results are shown in Table 3.
[0107] Table 3 Average recoveries and RSDs of mycotoxins from different M-SPE adsorbents
[0108]
[0109] The results show that the average recovery rate of Fe3O4@TAPT-COF-OH (2,3-dihydroxyterephthalaldehyde) is 61.2%-79.5%, the average recovery rate of Fe3O4@COF (TAPT-DHTA) (2,5-dihydroxyterephthalic acid) is 70.3%-81.0%, the average recovery rate of Fe3O4@TAPT-COF-C2H4 is 19.9%-32.5%, which is very low and less than 60% and cannot meet the detection requirements. The average recovery rate of Fe3O4@TAPT-COF-MeO is 49.6%-68.2%; and the average recovery rate of 4F-COF@Fe3O4 of the present invention is 98.2%-110.2%. Therefore, compared with magnetic adsorption materials prepared from other monomers, the 4F-COF@Fe3O4 of the present invention has a significantly superior adsorption and extraction effect on AFs.
[0110] The present invention does not need to use COOH-modified COOH-Fe3O4, and uses ordinary nano-Fe3O4 in a one-step method to directly prepare 4F-COF@Fe3O4. The method is simpler and is conducive to forming F-functionalized magnetic materials with a larger specific surface area, so that more active adsorption sites are fully exposed, which is conducive to the rapid adsorption and extraction of toxins and rapid and sufficient desorption. If the magnetization method of COOH-Fe3O4 is used, there will be greater steric hindrance, thereby reducing the specific surface area of magnetic F-COF to a greater extent, which is not conducive to the rapid combination of fungal toxins with the active sites of the adsorption and extraction materials, affecting the adsorption and extraction efficiency and desorption effect.
[0111] The 4F-COF-TAPT@Fe3O4 of the present invention has high adsorption capacity, good hydrophilicity, short adsorption equilibrium time, strong anti-matrix interference ability, good stability in the adsorption and extraction process, and has the advantages of fast separation speed, high adsorption and extraction efficiency, and many recycling times. The adsorption capacity, adsorption efficiency, desorption efficiency, etc. of existing materials such as Fe3O4@COF (TAPT-DHTA) are significantly improved.
[0112] The present invention successfully prepared superparamagnetic Fe3O4@F-COF. After adding the cut-off agent (aniline) once and adding the catalyst (Fe(NO3)3) in small amounts multiple times, it is conducive to the formation of magnetic F-COF equivalent to the pure F-COF crystal form, with an ultra-large specific surface area of 940m 2 / g, ensuring the stability of the adsorption and extraction materials. The magnetization method simplifies the tedious steps of SPE such as column packing and centrifugation, greatly simplifies the extraction steps, and improves the extraction efficiency.
Claims
1. Application of a fluorinated COF magnetic composite material in the adsorption of fungal toxins, wherein the fluorinated COF magnetic composite material is a nano-Fe3O4 particle as the core and a covalent organic framework material layer formed by condensation polymerization of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomer and 2,3,5,6-tetrafluoroterephthalaldehyde monomer connected by imine bonds is tightly attached to the nano-Fe3O4 particle.
2. The use according to claim 1, characterized in that: The fluorinated COF magnetic composite material is used as an adsorption material for adsorbing fungal toxins; or, the fluorinated COF magnetic composite material is used in preparing an adsorption material for adsorbing fungal toxins.
3. The use according to claim 1 or 2, characterized in that: The mycotoxins include aflatoxins.
4. The use according to claim 3, characterized in that: The aflatoxins include one or more of AFM1, AFB1, AFB2, AFG1, and AFG2.
5. The use according to claim 1, characterized in that: The molar ratio of the 2,4,6-tris(4-aminophenyl)-1,3,5-triazine monomer to the 2,3,5,6-tetrafluoroterephthalaldehyde monomer is 1:1-1.
5.
6. The use according to claim 1 or 5, characterized in that: The preparation method of the fluorinated COF magnetic composite material comprises: Mix 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 2,3,5,6-tetrafluoroterephthalaldehyde, o-dichlorobenzene and n-butanol, add aniline while mixing, and mix well; then add nano-Fe3O4 and mix well; then take a mixture of Fe(NO3)3 and n-butanol, add small amounts multiple times, mix well before and after each addition, and after all are added, ultrasonicate for 1h-1.5h, and then stand at 60℃-80℃ for at least 24h. The product is washed and dried to obtain a fluorinated COF magnetic composite material.
7. A sample processing method for mycotoxin detection, characterized in that: Includes steps: The sample is extracted with an acetonitrile aqueous solution to obtain a sample extract, which is blown dry and then redissolved with water to obtain a sample solution, the pH of which is adjusted to 5-8, the fluorinated COF magnetic composite material described in claim 1, 5 or 6 is added, mixed evenly for adsorption, and then the fluorinated COF magnetic composite material is separated using an external magnetic field; the fluorinated COF magnetic composite material separated using the external magnetic field is taken out after being eluted and desorbed by an eluent, and the eluent after desorption is used as a treated sample; The sample includes one or more of a food sample and a feed sample.
8. The sample processing method according to claim 7, characterized in that: The amount of fluorinated COF magnetic composite material used in each milliliter of sample solution is more than 1 mg; The adsorption time is more than 5 seconds; the desorption time is more than 1 minute.
9. The sample processing method according to claim 7, characterized in that: The eluent is selected from one of acetonitrile, acetonitrile aqueous solution, and acetonitrile acetic acid aqueous solution.
10. A method for detecting mycotoxins, characterized in that: The treated sample obtained by the sample processing method for mycotoxin detection according to any one of claims 7 to 9 is used as a test sample, and the mycotoxin detection method is used to detect the mycotoxin in the test sample.